2008
DOI: 10.1161/circulationaha.108.773838
|View full text |Cite
|
Sign up to set email alerts
|

Use of Cardiac Resynchronization Therapy in Patients Hospitalized With Heart Failure

Abstract: Background-The frequency and characterization of patients receiving cardiac resynchronization therapy (CRT) are largely unknown since the publication of pivotal clinical trials and subsequent incorporation of CRT into the American College of Cardiology/American Heart Association guidelines for heart failure. Methods and Results-We analyzed 33 898 patients admitted from January 2005 through September 2007 to 228 hospitals participating in the American Heart Association's Get With the Guidelines-Heart Failure pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
59
3
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 86 publications
(67 citation statements)
references
References 39 publications
4
59
3
1
Order By: Relevance
“…In an outpatient population with LVEF Յ35%, the Registry to Improve the Use of Evidence-Based Heart Failure Therapies in the Outpatient Setting (IMPROVE-HF) showed that older subjects, particularly older women, were significantly less likely to receive guideline-recommended CHF therapies. 19 The results of the American Heart Association's Get With the Guidelines-Heart Failure (GWTG-HF) program, extending the observation to devices, further supported this evidence, demonstrating also that women had a lower probability than men to receive CRT 20 and implantable cardioverter-defibrillators. 21 In our study, angiotensin-converting enzyme inhibitors or angiotensin receptor blockers and ␤ blockers were significantly underused, particularly at advanced age.…”
Section: Discussionmentioning
confidence: 89%
“…In an outpatient population with LVEF Յ35%, the Registry to Improve the Use of Evidence-Based Heart Failure Therapies in the Outpatient Setting (IMPROVE-HF) showed that older subjects, particularly older women, were significantly less likely to receive guideline-recommended CHF therapies. 19 The results of the American Heart Association's Get With the Guidelines-Heart Failure (GWTG-HF) program, extending the observation to devices, further supported this evidence, demonstrating also that women had a lower probability than men to receive CRT 20 and implantable cardioverter-defibrillators. 21 In our study, angiotensin-converting enzyme inhibitors or angiotensin receptor blockers and ␤ blockers were significantly underused, particularly at advanced age.…”
Section: Discussionmentioning
confidence: 89%
“…Other studies have suggested very little change in the use of these 3 therapies for HF from 2005 to 2008, making it less likely that the improvements observed were a result of secular trends. 6,7,16 Although the baseline rates of ␤-blocker use were reasonably high, there was still significant improvement at 24 Table 3.…”
Section: Discussionmentioning
confidence: 98%
“…Other studies have suggested very little change in the use of these 3 therapies for HF from 2005 to 2008, making it less likely that the improvements observed were a result of secular trends. 6,7,16 Although the baseline rates of ␤-blocker use were reasonably high, there was still significant improvement at 24 Those quality measures with lower baseline use showed greater absolute and relative improvement over time. These findings may reflect a greater effort to improve those measures with the best opportunities to improve, a ceiling effect on measures with higher levels of conformity, or other factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 Although ongoing trials continue to test the efficacy and safety of CRT in patient groups who were underrepresented or excluded from prior trials, the CRT evidence base is evolving and following the well-established pattern of investigation for technological advances in which health services researchers follow the clinical trialists into an area to evaluate the uptake, effectiveness, and safety of new technologies when deployed in routine clinical practice. As a first step in this process, the study by Piccini and colleagues 3 in this week's Circulation examines who is, and who is not, receiving CRT in routine clinical practice.…”
mentioning
confidence: 99%